Analisis Semiotika Charles Sanders Peirce Pada “Meme” Tentang Bahlil Lahadaila Di Akun Instagram @kementrianbakuhantam - Haisa Maru; Aka Kurnia SF (Journal of Literature Review, 2026)
The development of social media has encouraged the emergence of digital communication culture in the form of political satire memes as a means of criticizing public figures. One phenomenon that has attracted attention is the Bahlil Lahadalia meme uploaded by the Instagram account @kemetrianbakuhantam. These memes combine elements of humor, religious symbols, popular culture, and public policy issues that are developing in society. This research aims to analyze the meaning of signs in the Bahlil Lahadalia meme using Charles Sanders Peirce's semiotic theory. This research uses a descriptive qualitative approach with data collection techniques through observation and published documentation. Analysis is carried out through the classification of signs based on representation, object and interpretant to fulfill the relationship between signs, social reality and meaning built in memes. The research results show that the Bahlil Lahadalia meme contains elements of representation, object and interpretant which represent social criticism of the image of public officials, government policies and the dynamics of digital political communication. The creators use religious symbols, bureaucratic terms and visual satire to build criticism that is easy for the social media community to understand. Apart from that, memes also show the existence of digital culture related to virality and the attention economy on social media. Thus, it not only functions as digital entertainment, but also as a medium for social criticism and representation of political communication in cyberspace.